IMPLEMENTASI KEBIJAKAN PROGRAM PEMBINAAN ANAK JALANAN DI KOTA CIREBON ( STUDI KASUS DI DINAS SOSIAL, TENAGA KERJA DAN TRANSMIGRASI KOTA CIREBON ) - Gumilang Prakoso; Mukarto Siswoyo; Mohammad Sutarjo (Jurnal Ilmiah Publika, 2013)
An increasing number of street children in the city of Cirebon each year increasedsignificantly with the number of unemployment, it is a fundamental duty of the City ofCirebon particular Social Services, Manpower Cirebon to provide guidance to street children.Economic constraints, families are lacking in meeting the needs of the child, so the child hadasked to work on their own initiative or on the streets because of a very heavy burden onfamilies. By looking at the shortage faced by street children, the Government should take theCirebon City policy to provide guidance to the street children. The existence of street childrenpolicy development program conducted by the Department of Social Welfare, Manpower andTransmigration Cirebon City aims to foster the provision of street children in both the mental,spiritual and assistance for their needs so as to minimize their presence on the streets.However, the implementation of the development program of street children has not been inaccordance with what was expected, given the constraints faced by the lack of facilities suchas shelters for street children and the lack of funding coming from the center of the bottleneckto implement the program. For that reason, the author would like to see how theimplementation of the development program of street children is already realized well or not.This study, the authors used qualitative analysis methods to uncover deeper throughinterviews, and observations made and see how it goes and implementation obstaclesencountered. Based on research conducted by the author in the field it is seen that theimplementation of the development programs of street children in Social Services, ManpowerCirebon is good enough. Only the lack of facilities and funds to carry out the training forstreet children.